Psychometric Properties of the Bangla Version of the Stress and Anxiety to Viral Epidemics-6 Items Scale Among the General Population in Bangladesh - Ahmed, Oli; Hossain, Kazi Nur; Hiramoni, Fatema Akhter; Siddique, Rumana Ferdousi; Chung, Seockhoon (Frontiers in Psychiatry, 2022)
Background: Any disease outbreak creates psychological stress and anxiety among the public (e.g., Coronavirus Disease 2019 (COVID-19). There are several scales that assess anxiety specifically related to the COVID-19 pandemic. The Stress and Anxiety to Viral Epidemics-6 items (SAVE-6) scale is a reliable and valid tool to assess anxiety in any viral pandemic. The present study aims to validate the SAVE-6 scale in the Bangla language and culture, to assess such anxiety among the general Bangladeshi people. Methods: The SAVE-6 scale was translated into Bangla from English using the forward-backward translation procedure. A total of 357 Bangladeshi citizens participated via an online structured questionnaire. The items included questions on personal information, COVID-19 and vaccination, psychiatric history, the Bangla version of the SAVE-6 scale, the Generalized Anxiety Disorder-7 items (GAD-7) scale, and the Patient Health Questionnaire-9 items (PHQ-9) scale. Results: Both exploratory factor analysis and confirmatory factor analysis (CFA) were used to explore and confirm the single factor structure of the SAVE-6 scale in Bangla to be the same as that of the SAVE-6 scale. Multigroup CFA revealed invariance across sex, experience of being quarantined, experience of being infected, and presence of depression. Item analysis results showed good discrimination indices and internal consistency and reliability. The graded response model outputs also confirmed the validity and reliability of this scale, which had significant correlations with the GAD-7 and PHQ-9. Conclusion: Overall, the Bangla version of the SAVE-6 is a psychometrically good scale to assess viral pandemic-related anxiety.